ChemInform Abstract: Selenium‐Catalyzed C(sp3)—H Acyloxylation: Application in the Expedient Synthesis of Isobenzofuranones. Issue 37 (September 2015) - Kraetzschmar, Felix; Kassel, Martin; Delony, Daniel; Breder, Alexander
Abstract Starting from simple 2‐allyl benzoic acid derivatives an intramolecular oxidative acyloxylation is developed which provides a chemoselective access to isobenzofuranone skeletons representing the core structure of phthalide natural products and offer the opportunity for further derivatization.